Cross Reaction among Antibody Pili sub unit Hemagglutinin Proteins and Outer Membrane sub unit Hemagglutinin Proteins of Shigella flexneri - Avin Ainur Fitrianingsih; Lailia Nur Rachma; Alvi Milliana; Tinny Endang Hernowati; Aulanni'am Aulanni'am; Sanarto Santoso; Sumarno Reto Prawiro (Journal of Tropical Life Science, 2017)
Shigella  flexneri is the most common causal agent of shigellosis. Its pili are composed of pili protein subunits. Adhesion molecules can be found on the pili and outer membrane proteins (Omp). A hemagglutination reaction can be used for screening of adhesion molecules. Objectives: The purpose of this study was to determine the molecular weight of the pili protein subunits and outer membrane proteins of S. flexneri that act as hemagglutinin proteins, and to prove whether there is a cross-reaction between antibodies against hemagglutinin pili protein subunits and outer membrane proteins of S. flexneri. Methods: Pili protein subunits were isolated using pili bacteria cutters, and the outer membrane proteins were solubilized and obtained using sodium dodecyl sulfate 0.05% as detergent for Omp isolation.  The hemagglutination reaction used mice erythrocytes. The cross reactions between subunit pili proteins were conducted by Western blot and Dot blot. Results:. Antibodies against hemagglutinin sub unit pili protein 18 kDa responded to pili protein subunits 18 kDa; 23 kDa; 34 kDa; and 53 kDa; and Omp 23 kDa and 27 kDa. Omp and subunit pili proteins S. flexneri consists of several identical epitopes  that were responsible for the similarity of the response profile in the cross-reactions of antibodies.